Biomass and Nutrition Content of Silk Woms (Tubifex sp.) on the Substrate of Germented Chicken Manure - Anita, Putri; Widiastuti, Irawati Mei (FAPETKAN UNTAD, 2021)
Silk worms (Tubifex sp.) are a natiral food that is wederly used in larvae and fish seed hatchry in the aquaculture industry, with the use of silk worms which are still dominated by the catch of dialar so that there activities result in a decrease in production in nature while the demand for silk worms. It is quite high, one of the offerts to meet the availability of silk worms as natural food for the cultivation process, silkworm culture is crreid out. The succes of silk worm culture is detrmined by the culture media containing organic and non-organic materilas such as fermented chichen manure, rice baran and tofu dregs. This study pims to deterimine the effect of using the substrate with the additon of termented chicken manure on the grouth of biomass and nutrient content of silk worms (Tubifex sp.). This study was conducted from August 2020 to October 2020 at the Laboratory of Water Quality and Aquatic Biology, Faculty of animal Husbandry and Fisheries, Tadulako University. Hammer. The silk worms that are cultured are silk worms taken from nature under the bridge II Palu Jl I Gusti Ngurah Rai, Tawanjuka, Kec. South Palu City. Central Sulawesi Province. This study was designed using a completely randomized design wiht 4 treatment of 5 replication in order to obtain 20 experimental units. Experiments were carried out to see the growth rate of biomass and nutrient content of silkworm (Tubifex sp.) from the culture process on the substrate of fermented chiken manure, rice bran and tofu pulp. The results showed that the process of biomass growth and good nutritional content was found in the treatment where the amount of substrate was 50 g/L of fermented chicken manure, 50g tofu and 100g of rice bran.